Transition metal rates in latosol twice treated with sewage sludge - Pigozzo,Ana Tereza Jordão (2006)
Agricultural recycling of sewage sludge has been a source of accumulation of heavy metals in the environment which may reach toxic levels and cause serious damage to the biota. Field experiments were undertaken for two agricultural years (2000 and 2002) and effects of two sewage sludge applications were evaluated through the extraction of (essential and non-essential) transition metals by diethylenetriaminepentaacetic acid (DTPA) extractor in a medium texture dystrophic Dark Red Latosol. Cd, Ni, Co, Pb and Cr were not detected. Application of sewage sludge initially caused a slight pH rise in the soil; later pH lowered and kept itself close to the starting level. It could be concluded that through consecutive sludge application, extractable rates of Fe and Mn in soil samples gradually increased during the two agricultural years in proportion to sewage sludge doses and sampling period. In fact, they were higher than rates of control. Due to low concentrations of soil samples, extractor had a restricted capacity for evaluation of its phytoavailability.